FRIENDSHIP IN JACK LONDON’S THE CALL OF THE WILD - Lumowa, Clement; Liando, Nihta; Maukar, Merlin (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This study aims to reveal the friendship in Jack London’s The Call of the Wild. It is qualitative research, with the data used being primary sources and secondary. Primary data was taken from the quotes from the novel, and secondary was from articles, journals, books, and the internet related to the analysis. The objective approach by M. H. Abrams was used in analyzing the data. Based on the analysis, it was found that the friendship between Buck and Thornton was revealed in some settings and times. Their friendship revealed to admire one another’s good qualities with sympathy, generosity, fairness, and courage of the friend, while the characteristics of their friendship revealed in this novel were voluntary, personal relationship, affective bond, and mutual and equal relationship. This study primarily found their friendship revealed in four contexts: They supported and protected each other, showed affection, were faithful towards each other, and they shared good and bad moments. It is suggested that future researchers may use the objective approach to analyze the themes in this novel since the approach is considered appropriate for analyzing the intrinsic parts of the literary works. The future researcher may also analyze other interesting themes or elements of the novel with the same approach or the same theme with a different approach.